Effects of compound yeast culture on growth performance, antioxidant function and inflammatory factors of Hu sheep - Liu, Shixiong; Ma, Jiabin; Yang, Lan; Chen, Hui; Li, Xueqiang; Du, Rui; Xue, Chen; Liu, Dacheng (Frontiers in Veterinary Science, 2025)
IntroductionThe purpose of this study was to investigate the effects of compound yeast culture on production performance, antioxidant function, and inflammatory factors in Hu sheep.MethodsA total of 180 45-day-old healthy Hu sheep were randomly divided into two groups. The control group was fed a basal diet, and the experimental group was supplemented with 50 g/kg compound yeast culture during the conservation period (1–30 days) and 60 g/kg during the fattening period (31–117 days). The experiment lasted 124 days, with a pre-feeding period of 7 days and a formal period of 117 days. Daily feed intake was recorded, and the animals were weighed before morning feeding on days 1, 36, 67, 97, and 117 of the experiment and slaughtered on the 117th day. At the same time, non-anticoagulant blood was collected before morning feeding on days 1, 30, 60, and 90, and serum antioxidant indices and serum inflammatory factors were measured.ResultsThe results showed that the average daily gain of Hu sheep in the experimental group increased by 38 g compared to that in the control group, which increased by 13.4% (p < 0.05). The average daily feed intake of the experimental group increased by 80 g, an increase of 5% (p < 0.05). The feed-to-weight ratio in the experimental group decreased by 8.3% (p < 0.05). Compared with the control group, the economic profit of the experimental group increased by 130.27 yuan, an increase of 34.6% (p < 0.01). The serum total antioxidant capacity (T-AOC) content and superoxide dismutase activity (SOD) activity of Hu sheep in the experimental group significantly increased (p < 0.05). The malondialdehyde (MDA) content decreased significantly (p < 0.01). The contents of inflammatory factors TNF-α, IL-6, IL-4 and IL-10 in the serum of Hu sheep in the experimental group were significantly increased (p < 0.05).DiscussionThe above results showed that compound yeast culture significantly increased Hu sheep’s feed intake, daily gain, and economic benefit, and significantly reduced the feed-to-weight ratio, improved the antioxidant capacity, improved the immune function, and alleviated the effect of stress on Hu sheep.